METASOMATIC ROCKS AND GENESIS OF THE SKRYTOE SCHEELITE DEPOSIT (PRIMORSKI KRAI) - Gvozdev V.I.; Orekhov A.A. (My University, 2004)
The mineral composition of metasomatic rocks and ore veinlets was studied at the Skrytoe scheelite deposit (Malinovsk ore field, Primorski Krai). Their mineral types and associations were distinguished, and the chemical compositions of rocks were characterized. The genesis of scheelite mineralization is discussed on this basis, and the studied mineralization is compared with that of the well-studied Vostok-2 and Lermontovsk deposits. I